1993
DOI: 10.1007/bf00999080
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a respiratory resistance biofeedback training

Abstract: This study evaluated the effectiveness of a respiratory resistance biofeedback training. Fifteen adult asthmatic subjects participated in a feedback training program including twelve feedback sessions (three sessions weekly). Respiratory resistance (Ros) was measured using the forced oscillation method; to prevent subjects from lung hyperinflation, feedback was interrupted when functional residual capacity increased. One-second forced expiratory volume (FEV1), usage of self-administered medication, degree of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Mass and his colleagues (1991) attempted to directly train participants to decrease respiratory resistance by providing continuous biofeedback of this measure, using the forced oscillation method. In an uncontrolled trial, this feedback technique decreased average respiratory resistance within sessions but not between sessions (Mass, Dahme, & Richter, 1993), and it did not increase FEV 1 (Mass, Richter, & Dahme, 1996). They concluded that this type of biofeedback might not be an effective treatment component against bronchial asthma in adults.…”
Section: Biofeedback Techniquesmentioning
confidence: 97%
“…Mass and his colleagues (1991) attempted to directly train participants to decrease respiratory resistance by providing continuous biofeedback of this measure, using the forced oscillation method. In an uncontrolled trial, this feedback technique decreased average respiratory resistance within sessions but not between sessions (Mass, Dahme, & Richter, 1993), and it did not increase FEV 1 (Mass, Richter, & Dahme, 1996). They concluded that this type of biofeedback might not be an effective treatment component against bronchial asthma in adults.…”
Section: Biofeedback Techniquesmentioning
confidence: 97%
“…Each of these approaches has its own specific set-up of sensors and follows a different psychophysiological rationale. Findings with direct feedback of respiratory resistance (controlled for hyperinflation of the lungs, which can reduce resistance), one of the most relevant parameters of asthma pathophysiology, were disappointing (Mass, Dahme & Richter, 1993). Similarly, electromyography-supported facial muscle relaxation that has been promoted in earlier research has been found questionable in its rationale and empirical outcome (Ritz, 2004).…”
Section: Behavioral Medicine Treatment Approaches For Asthmamentioning
confidence: 99%
“…In particular, skeletal muscle activity is an integral part of the behavioral process itself and an essential component of many psychological phenomena~Cacioppo, Tassinary, & Fridlund, 1990!. With a growing number of studies investigating the psychophysiology of respiratory resistance~Butler & Steptoe, 1986;Carr, Lehrer, Jackson, & Hochron, 1996;Dahme, Richter, & Masz, 1996;Kotses, Westlund, & Creer, 1987;Masz, Richter, & Dahme, 1993;Wigal, Kotses, Rawson, & Creer, 1988!, it is thus critical to explore the potential role of skeletal muscle activation on this parameter.…”
mentioning
confidence: 99%